PSYCHOLOGICAL CAPITAL DAN KECUKUPAN ANGGARAN SEBAGAI MEKANISME PENINGKATAN PROSES PARTISIPASI ANGGARAN UNTUK MENCAPAI KINERJA MANAJERIAL - Lenny Kawandy; Oktavianus Pasoloran; Suwandi Ng (Magister Akuntansi, Universitas Atma Jaya Makassar, 2019)
This study aims to investigate the role of Psychological Capital and budget adequacy in mediating the effect of budget participation on managerial performance. The sample used in this study is a Real Estate company registered in REI Makassar, South Sulawesi. Sample selection in this study using purposive sampling method based on certain criteria. The results of the study using path analysis shows that budget participation has a positive effect on psychological capital and budget adequacy, Sobel testing indicates that psychological capital can mediate the effect of budgetary participation on managerial performance, but budget adequacy does not mediate the relationship between budgetary and managerial participation.